Respuesta :
The first thing you should do is verify that the ordered pairs satisfy equality. If so, then that pair ordered belongs to the line. Let us begin:
3x-4y = 9
(-1.3)
3 (-1) -4 (3) = 9
-3-12 = 9
-15 = 9 (Does not belong)
(2/3, -7 / 4)
3 (2/3) -4 (-7/4) = 9
6 + 28 = 9
34 = 9 (Does not belong)
(-5, -6)
3 (-5) -4 (-6) = 9
-15 + 24 = 9
9 = 9 (Yes, it belongs)
(1, -3 / 2)
3 (1) -4 (-3/2) = 9
3 + 6 = 9
9 = 9 (Yes, it belongs)
answer
ordered pairs are
(-5, -6)
(1, -3 / 2)
3x-4y = 9
(-1.3)
3 (-1) -4 (3) = 9
-3-12 = 9
-15 = 9 (Does not belong)
(2/3, -7 / 4)
3 (2/3) -4 (-7/4) = 9
6 + 28 = 9
34 = 9 (Does not belong)
(-5, -6)
3 (-5) -4 (-6) = 9
-15 + 24 = 9
9 = 9 (Yes, it belongs)
(1, -3 / 2)
3 (1) -4 (-3/2) = 9
3 + 6 = 9
9 = 9 (Yes, it belongs)
answer
ordered pairs are
(-5, -6)
(1, -3 / 2)
For any given equation the points must satisfy the RHS and LHS
Solution:-
Hence to prove the equation 3x-4y=9; --1
1.Therefore sub (-1, 3 ) = (x,y ) ie x=-1 ; y=3
sub in 1 we get -3-12=-15 not equal to 9(RHS) it is not the req point.
2.Similarly sub (2/3,â’7/4 ) = (x,y ) ie x=2/3 ; y=â’7/4
sub in 1 we get 3(2/3)- 4(-7/4) = 2+7=9 is equal to 9 (RHS) hence it is the req point.
3. Similarly sub (â’5,â’6) = (x,y ) ie x=-5 ; y=â’6
sub in 1 we get 3 (-5) -4(-6) =-15 +24 = 9 is equal to 9 (RHS) hence it is the req point.
4.Similarly sub (1,â’3/2) ​ = (x,y ) ie x= 1; y=â’3/2
sub in 1 we get 3 (1) - 4(â’3/2) = 9 is equal to 9 (RHS) hence it is the req point.
Ans : -
The required points are (2/3,â’7/4) ​ ​ (â’5,â’6) ​ (1,â’3/2)